Application of QUEFTS Model for Site-Specific Nutrient Management of NPK in Sweet Potato (Ipomoea batatas L. Lam). Issue 13 (5th August 2016) - Kumar, Prince; Byju, G.; Singh, B. P.; Minhas, J. S.; Dua, V. K.
ABSTRACT: Sweet potato productivity in India is either stagnated or lowering down over the past many years. The main reasons for low yield are conventional blanket recommendation of fertilizers, lower nutrient-use efficiency and imbalance in the use of fertilizers. Recommendation of major nutrients, nitrogen, phosphorus, and potassium (NPK), based on quantitative approaches will augment sweet potato production per unit area by increasing the nutrient-use efficiency. The present study calibrated the Quantitative Evaluation of Fertility of Tropical Soils (QUEFTS) model for the estimation of NPK requirements and fertilizers recommendations for different target yields of sweet potato. The QUEFTS basically works on the principle of NPK nutrient interactions and climate-adjusted yield potential of a region. Published data sets from several field experiments related to NPK carried out till date were collected to reflect the environment variability. The results of the present study showed that to produce one ton tuber, 16:6:18 kg N, P, and K, respectively, would be needed with the internal efficiencies of 61:167:57 kg tubers kg −1 NPK removed. The maximum accumulation and dilution (kg tuber kg −1 nutrient removed) of N (40, 80), P (96, 272), and K (30, 85) were also derived as standard parameters in QUEFTS for optimum fertilizer recommendation in tropical and subtropical regions of India. The observed yields of sweet potato with different amounts of nutrients were in agreement with the values predicted by the model. Therefore, it is utmost important to have the results of the study validated in major growing environments of India for fertilizer recommendation in sweet potato.